A REGISTER ANALYSIS IN ONLINE SHOP TERM FACEBOOK - Corrie Yuliana Lubis; Erwin Ashari; Warno Edi (English Department, University of Riau Kepulauan, Batam,Indonesia, 2016)
The aims of this research are to find out the terms that are categorized as register used in Online shops community in social media. The method of this research is descriptive qualitative research where the writer describes holistically the use of the register by the online shops in facebook. The object of this research is the register used in online shops. Based on the analysis the researcher finds the data the result of the study show the total amount of register found in this research is 100 register in the found online shops facebook. There are 11 register identified as abbreviations, 13 for clippings, 3 coinages, 2 acronyms, 8 compoundings, 35 borrowings, 28 phrase, 45 registers functioned as consultative, 16 register as deliberative, 14 register as casual, 6 register as intimate, 2 register as oratorical or frozen. Consultative and deliberative are the dominant functions of the register used by the online shops but consultative is the most dominant function according to research. As stated in the problem statements, those of the matters relating to the business world would be very easy to find. For example ongkir, disc, call, etc.Keywords : Register, Register Functioned, Consultative and Deliberative, Online Shops ( Facebook )